2016
DOI: 10.1101/069278
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Dynamic representation of time in brain states

Abstract: The ability to process time on the scale of milliseconds and seconds is essential for behaviour. A growing number of studies have started to focus on brain dynamics as a mechanism for temporal encoding. Although there is growing evidence in favour of this view from computational and in vitro studies, there is still a lack of results from experiments in humans. We show that high-dimensional brain states revealed by multivariate pattern analysis of human EEG are correlated to temporal judgements. First, we show … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 34 publications
0
8
0
Order By: Relevance
“…In a recent study, we have shown that multivariate pattern analysis (MVPA) can reveal spatiotemporal dynamics of human brain activity related to temporal processing 14 . Multivariate approaches can take advantage of small differences in the signal across electrodes that might not be detectable using classical EEG methods.…”
Section: Introductionmentioning
confidence: 99%
“…In a recent study, we have shown that multivariate pattern analysis (MVPA) can reveal spatiotemporal dynamics of human brain activity related to temporal processing 14 . Multivariate approaches can take advantage of small differences in the signal across electrodes that might not be detectable using classical EEG methods.…”
Section: Introductionmentioning
confidence: 99%
“…This design enabled to address the possibility of internal timing or duration being explicitly available to awareness through self-referential metacognition (Block, 1995;. Because current neuroscientific models posit that internal dynamics in timing are mediated by oscillatory or statedependent network dynamics (Laje & Buonomano, 2013;Karmarkar & Buonomano, 2007;Buhusi & Meck, 2005;Merchant et al, 2013;Allman et al, 2014;Gu et al, 2015;van Wassenhove, 2016;Bueno et al, 2017), we combined magneto-and electroencephalography (M/EEG) to quantify the dynamics of oscillatory brain responses when participants engaged in self-generated and self-assessed timing. Using a temporal production task to assess metacognition provided several paradigmatic and conceptual benefits.…”
Section: Introductionmentioning
confidence: 99%
“…In previous works, we have shown that time-related information was decodable from pre-offset EEG signals in temporal reproduction [Barne et al, 2018] and temporal categorisation tasks [Bueno et al, 2017]. However, because in our previous categorisation task there was only one reference interval [Bueno et al, 2017], time and decision information were intrinsically correlated. In the present study, we show again that it is possible to decode time-related information from within each condition.…”
Section: Discussionmentioning
confidence: 69%
“…Responses were collected via a response box with 9 buttons (DirectIN High Speed Button; Empirisoft). The task consisted of a computerised "shoot the target" task adapted from Guilhardi et al [2010] and Bueno et al [2017].…”
Section: Stimuli and Proceduresmentioning
confidence: 99%
See 1 more Smart Citation